Sistem Informasi Pengelolaan Persediaan Barang Berbasis Web Pada Toko Bangunan Sentosa Bersama Menggunakan Metode Extreme Programming - Edwardo; Nita Rosa Damayanti (PPPM Institut Teknologi Pagar Alam, 2025)
In today's digital era, inventory management is crucial for business operations, especially in retail industries such as building supply stores. Inventory management is the art of managing the flow of goods within a company, including building supply stores. The availability of a complete and varied range of goods makes Sentosa Bersama Building Store an integrated solution for construction needs in the region. The problem at Sentosa Bersama Building Store is that inventory management is still carried out manually, which often results in unsystematic management and control of inventory information. This situation requires an information system that can address this issue. Because it is easily accessible via the internet, a web-based information system can be the most effective and up-to-date way to provide information. Businesses can use this system to better manage product inventory data. The system development method used by the author is Extreme Programming. With the web-based inventory management information system at Sentosa Bersama Building Store using the Extreme Programming method, all activities can be well controlled.